The development of problem-based learning worksheets to facilitate mathematical problem-solving skills in relation and function topics - Yanti, Risma; Hutapea, Nahor Murani; Anggraini, Rini Dian (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
This research aims to develop student worksheets for eighth-grade mathematics, focusing on the topics of Relations and Functions, using a Problem-Based Learning approach. The development process followed the 4D model, which includes the stages of defining, designing, developing, and disseminating. The research instruments used were validation sheets and student questionnaires. After the preparation stage, the worksheets were evaluated by three validators and revised based on the feedback received. Data analysis showed an average validation score of 89.12%, indicating a very high level of validity. Subsequently, the validated worksheets were tested on a small group of students, resulting in a practicality score of 80.28%, which is classified as very practical. This research successfully produced valid and practical worksheets for eighth-grade mathematics, particularly in the topics of relations and functions.